2010
DOI: 10.1177/0885328210367442
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Polycaprolactone by Biomacromolecules and their Blood Compatibility

Abstract: Improving blood compatibility of biodegradable polymers is an area of intensive research in blood contacting devices. In this study, curdlan sulphate and heparin-modified poly (caprolactone) (PCL) hybrids were developed by physically entrapping these molecules on the PCL surface. This modification technique was performed by reversible gelation of the PCL surface region following exposure to a solvent and nonsolvent mixture. The presence of these biomacromolecules on the PCL surface was verified by atomic force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 42 publications
0
32
0
1
Order By: Relevance
“…Surface chemistry is also known to impact the in vivo response to the injected materials [1215]. For example, polyurethane functionalized with zwitterionic or anionic functional groups showed lower in vivo inflammatory reaction than those functionalized with cationic chemistries [16]. Similarly, polypropylene particles coated with carboxylic acid groups were less inflammatory than those coated with amine or hydroxyl groups [14].…”
Section: Introductionmentioning
confidence: 99%
“…Surface chemistry is also known to impact the in vivo response to the injected materials [1215]. For example, polyurethane functionalized with zwitterionic or anionic functional groups showed lower in vivo inflammatory reaction than those functionalized with cationic chemistries [16]. Similarly, polypropylene particles coated with carboxylic acid groups were less inflammatory than those coated with amine or hydroxyl groups [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the swelling method [38], [39] the silver nanoparticles solution (10 ml) is poured on the polymer film (5 cm 2 ) which is placed in a Teflon plate. Since the solution has THF, the polymer gets swollen and the nanoparticles penetrate into it.…”
Section: Methodsmentioning
confidence: 99%
“…This practice, can lead to adverse drug reactions as well as produce resistant microorganisms. Better infection prevention strategies include the use of antibiotic or antimicrobial coatings on device surfaces [20], [21] and impregnation of device components with antibacterial silver [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khandwekar et al compared leukocyte adhesion on bare PCL surfaces and modulated PCL surfaces. They showed that leukocyte adhesion on bare PCL could even be more reduced when converting to a heparin-modified PCL [200].…”
Section: Interactions Of Tissue-and Blood-cells With the Polymer Surfmentioning
confidence: 99%